2008
DOI: 10.1111/j.1582-4934.2008.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil‐mediated neovascularization and protection against myocardial ischaemia reperfusion injury in rats: role of VEGF/angiopoietin‐1

Abstract: Sildenafil citrate (SC), a drug for erectile dysfunction, is now emerging as a cardiopulmonary drug. Our study aimed to determine a novel role of sildenafil on cardioprotection through stimulating angiogenesis during ischaemia (I) reperfusion (R) at both capillary and arteriolar levels and to examine the role of vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang-1) in this mechanistic effect. Rats were divided into: control sham (CS), sildenafil sham (SS), control + IR (CIR) and sildenafil + IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 49 publications
5
74
1
Order By: Relevance
“…In particular, sildenafil was developed to mimic the pharmacological action of NO by increasing intracellular cyclic guanosine 39,59-monophosphate (cGMP) concentrations. Ladha and colleagues (19) demonstrated that sildenafil improves alveolar growth and ameliorates BPD-associated pulmonary hypertension in rats with BPD, and sildenafil was also reported to ameliorate BPD symptoms by augmenting the neovascularization mediated by VEGF and angiopoietin-1 (20). Currently, sildenafil is undergoing clinical trials as a BPD therapeutic regimen (21,22).…”
mentioning
confidence: 99%
“…In particular, sildenafil was developed to mimic the pharmacological action of NO by increasing intracellular cyclic guanosine 39,59-monophosphate (cGMP) concentrations. Ladha and colleagues (19) demonstrated that sildenafil improves alveolar growth and ameliorates BPD-associated pulmonary hypertension in rats with BPD, and sildenafil was also reported to ameliorate BPD symptoms by augmenting the neovascularization mediated by VEGF and angiopoietin-1 (20). Currently, sildenafil is undergoing clinical trials as a BPD therapeutic regimen (21,22).…”
mentioning
confidence: 99%
“…9 This is supported by compelling evidence from animal models indicating that the PDE5is such as sildenafil, tadalafil and vardenafil are cardioprotective in ischaemia-reperfusion injury (IRI) while suppressing cardiac arrhythmias and improving cardiac function. [10][11][12][13][14][15] Furthermore, small randomised controlled trials (RCTs) in systolic heart failure have shown an improvement in haemodynamic parameters and functional indices. 16 It is therefore important to establish whether there is benefit or harm in highrisk patients with ED.…”
mentioning
confidence: 99%
“…Its mechanism of action involves inhibition of the breakdown of cyclic GMP, which in turn leads to local vasodilation. Recently, sildenafil has also been shown to increase expression of vascular endothelial growth factor and angiopoietin-1, leading to increased neovascularization in a rat model of coronary ischemia and promoting functional recovery after stroke in a rat model of cerebral ischemia [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…cGMP has been implicated in post-natal angiogenesis. Sildenafil citrate leads to increased vascular endothelial growth factor expression and angiogenesis in a rat model of coronary ischemia [6]. In addition, administration of oral sildenafil citrate improved recovery of spontaneous 'normal' erections following radical prostatectomy in a controlled study [7].…”
Section: Introductionmentioning
confidence: 99%